Universal Urogynecologic Consultation and Screening for Fecal Incontinence in Pregnant Women With a History of Obstetric Anal Sphincter Injury: A Cost-Effectiveness Analysis. Issue 3 (10th March 2023) - Swallow, Christina H.; Harvey, Christina N.; Harmanli, Oz; Shepherd, Jonathan P.
Abstract : Importance: Obstetric anal sphincter injuries (OASIS) predispose for the development of fecal incontinence (FI), but management of subsequent pregnancy after OASIS is controversial. Objective: We aimed to determine if universal urogynecologic consultation (UUC) for pregnant women with prior OASIS is cost-effective. Study Design: We performed a cost-effectiveness analysis of pregnant women with a history of OASIS modeling UUC compared with no referral (usual care). We modeled the route of delivery, peripartum complications, and subsequent treatment options for FI. Probabilities and utilities were obtained from published literature. Costs using a third-party payer perspective were gathered from the Medicare physician fee schedule reimbursement data or published literature converted to 2019 U.S. dollars. Cost-effectiveness was determined using incremental cost-effectiveness ratios). Results: Our model demonstrated that UUC for pregnant patients with prior OASIS was cost-effective. Compared with usual care, the incremental cost-effectiveness ratio for this strategy was 19, 858.32 per quality-adjusted life-year, below the willingness to pay a threshold of 50, 000/quality-adjusted life-year. Universal urogynecologic consultation reduced the ultimate rate of FI from 25.33% to 22.67% and reduced patients living with untreated FI from 17.36% to 1.49%. Universal urogynecologic consultation increased the use of physical therapy by 14.14%, whereas rates of sacral neuromodulation and sphincteroplasty increased by only 2.48% and 0.58%, respectively. Universal urogynecologic consultation reduced the rate of vaginal delivery from 97.26% to 72.42%, which in turn led to a 1.15% increase in peripartum maternal complications. Conclusions: Universal urogynecologic consultation in women with a history of OASIS is a cost-effective strategy that decreases the overall incidence of FI, increases treatment utilization for FI, and only marginally increases the risk of maternal morbidity.